ARTiFICe - Augmented Reality Framework for Distributed Collaboration - Mossel, Annette; Schönauer, Christian; Gerstweiler, Georg; Kaufmann, Hannes (International Journal of Virtual Reality, 2012)
This paper introduces a flexible and powerful software framework based on an off the shelf game engine which is used to develop distributed and collaborative virtual and augmented reality applications. We describe ARTiFICe’s flexible design and implementation and demonstrate its use in research and teaching where 97 students in two lab courses developed AR applications with it. Applications are presented on mobile, desktop and immersive systems using low cost 6-DOF input devices (Microsoft Kinect, Razer Hydra, SpaceNavigator), that we integrated into our framework.